Pendampingan peningkatan kemampuan bahasa Inggris siswa panti asuhan Dayang Dermah Bengkalis - Rini Fitria; Ervina Ervina; Kurniati Kurniati; Riki Astafi (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
In addition to studying in formal schools, children can also study in non-formal schools, such as taking courses to understand a lesson. However, to be able to take the course certainly costs a lot. The symptoms found were that some students came from underprivileged families. Found it difficult to divide their study time with their busy lives at the orphanage, lacked interest in learning English, and did not have English language manuals other than textbooks from school. This service activity aims to improve students' English through courses at the Dayang Dermah Bengkalis Orphanage. The method used in this service activity is through fun courses in games, singing, and short conversations. The result of this service is that students' English skills have increased with this course, as evidenced by the increase in students' average English scores from 78 on the initial test to 87 on the final test. It can be concluded that using the course method is an effective way to Improving Students' English at Dayang Dermah Bengkalis Orphanage.